PENINGKATAN GIZI IBU HAMIL DENGAN FORMULA MULTI GIZI DALAM UPAYA UNTUK MENINGKATKAN PERTUMBUHAN, PERKEMBANGAN MENTAL DAN MOTORIK BAYI - Haslinda, Haslinda (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACTThis study aims to assess the effect of multi-nutrient supplement efforts to provide pregnant women with fetal growth and birth growth also for the mental and motor development of infants. The research was conducted over three stages; the first year of this study has been tested to the mice. The research was carried out on pregnant women in the District Tobasa. Sample of 60 people and were treated for 9 months to pregnant women to bear children. Design research to be conducted is a prospective epidemiologic design (cohort studies) in the form of the intervention and comparison (control) were given control of the sample selected randomly, so called "A Community Randomized Trial". Framework instance is newly pregnant mother. Research findings on the socio-economic (age KK, aged mother, KK Education, Education Mother, Food Science, BMI) did not differ between groups P <0.05. Nutritional Biochemistry Fropil initial blood (HB, Ferrit, Zn, FT4, TSH, Folate, Vit. A) No difference between groups, P <0.05. Nutrient intake of biscuits for intervention / day (Energy, Fat, Protein, Carbohydrates, Fe, Zinc, Iodine, Folate, Vit A) is not different between treatment groups P <0.05 except Vit A. BB gain during pregnancy on the treatment intervention 1, 2, 3 (not different, P <0.05. Weight Infants Born on 1, 2, 3 treatment also did not differ (P <0.05. Length bodies (PB) and Head Circumference (LK), Bust (LD) was also not different, P <0.05). Multivariate Regression Analysis of the main factors that affect the accretion BB is that BB Pregnant women were early pregnancy. Primary factor affecting pregnant women BBL is that BB was added. Though generally biscuit Multi Nutrient supplementation had no significant effect pregnancy on the growth and development of infants, however, tend to relate positively and improve the nutritional status of the mother before the birth of biochemistry. Initial sample size was relatively small (20/group) and about 15% lost to follow-up. Ideally biscuit was given daily but this study was only able to provide 3 times a week. Kata Kunci : Gizi, ibu hamil, mental motorik bayi.